Sub-commanderies in the Aragonese Province of the Templars - Forey, Alan (The journal of medieval monastic studies, 2022)
In the Aragonese province of the Templars, as elsewhere in the West, it was the practice for brothers to be placed in charge of sections of a convent’s lands, thus creating sub-commanderies. Those appointed usually held office for only short terms and were usually brother sergeants. But there was no attempt to establish a uniform system: some convents had many more sub-commanderies than others; some sub-commanderies had only a brief existence, while others can be traced over long periods; the buildings in which they were based varied widely (only a few had chapels), as did the numbers of brothers and non-Templars residing in them; and the powers exercised by sub-commanders appear not always to have been the same.